2020
DOI: 10.1073/pnas.1917869117
|View full text |Cite
|
Sign up to set email alerts
|

Sea-level rise and the emergence of a keystone grazer alter the geomorphic evolution and ecology of southeast US salt marshes

Abstract: Keystone species have large ecological effects relative to their abundance and have been identified in many ecosystems. However, global change is pervasively altering environmental conditions, potentially elevating new species to keystone roles. Here, we reveal that a historically innocuous grazer—the marsh crab Sesarma reticulatum—is rapidly reshaping the geomorphic evolution and ecological organization of southeastern US salt marshes now burdened by rising sea levels. Our analyses indicate that sea-level ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 82 publications
2
65
1
Order By: Relevance
“…The rapid rate of tidal creek extension in RSLR‐affected marshes could result from an increased tidal prism (Stefanon et al 2012), or accelerated bioturbation. Studies in several Southeastern U.S. marshes found that dieback of vegetation coupled with intense burrowing by crabs produces a bare and topographically depressed region beyond the channel head toward which the channel head extends (Hughes et al 2009; Crotty et al 2020). In a mid‐Atlantic Spartina alterniflora saltmarsh, Wilson et al (2012) found oxidized conditions in the upper 10–15 cm of the marsh induced by crab burrowing causes enhanced degradation of S. alterniflora belowground biomass, which reduces the structural integrity of the soil, increases the erosion potential of the sediment in creek head areas, and ultimately facilitates creek extension in order to accommodate tidal flows.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid rate of tidal creek extension in RSLR‐affected marshes could result from an increased tidal prism (Stefanon et al 2012), or accelerated bioturbation. Studies in several Southeastern U.S. marshes found that dieback of vegetation coupled with intense burrowing by crabs produces a bare and topographically depressed region beyond the channel head toward which the channel head extends (Hughes et al 2009; Crotty et al 2020). In a mid‐Atlantic Spartina alterniflora saltmarsh, Wilson et al (2012) found oxidized conditions in the upper 10–15 cm of the marsh induced by crab burrowing causes enhanced degradation of S. alterniflora belowground biomass, which reduces the structural integrity of the soil, increases the erosion potential of the sediment in creek head areas, and ultimately facilitates creek extension in order to accommodate tidal flows.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of plants around the creek head increases access to the marsh surface by nekton, increasing predation rates (Crotty et al. 2020). In natural creeks, Spartina that revegetates along the back of the creek head and the new creek is tall and vigorous, as is typical of creek‐bank plants (Valiela et al.…”
Section: Discussionmentioning
confidence: 99%
“…Even earthworm fronts advance at up to 5 m/yr (Silliman et al 2013). In contrast, Sesarma fronts expand slowly, at˜2 m/yr (Hughes et al 2009, Crotty et al 2020. This is a distance that an individual crab could traverse in less than a minute, indicating that movement of the front is constrained by factors other than mobility of the crabs.…”
Section: Introductionmentioning
confidence: 98%
“…In Elkhorn Slough, it is likely that the positive effect of burrows is due to increased drainage [58] and reduced waterlogging stress [59], which outweighs any possible negative effects. Top-down effects on vegetation can be very strong [61][62][63], but such effects will always interact with physical factors and thus may vary in strength (i.e. snail grazing in marshes with drought [64], pollinator and herbivore interactions with plants across environmental gradients [65], foraging behavior of coral reef fishes with distance from reef [66]).…”
Section: Multiple Local Factors Drive Interior Marsh Dynamicsmentioning
confidence: 99%